(untitled) (Anclajes, 2024)
A recurring element in Ricardo Piglia’s poetics is the inherent relationship between literary criticism and fiction, with regards to the various discursive registers in his work, which brings together discursive genres such as the prologue, the diary, the interview, television classes or the arguments about literature made by characters in his novels. This article analyzes this relationship by examining the thirteen prologues Piglia wrote for Serie del Recienvenido between 2012 and 2015, through an approach that focuses on its use of the combinative process. This allows us to return and revise discussions about literary tradition and renewal.